An Empirical Study of Microsoft Copilot Adoption in Financial Technology: Productivity, Performance, and Trust Perspectives - Batmaca, Volkan; Cubukcu Cerasi, Ceren (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This chapter presents an empirical study examining the determinants of Microsoft Copilot usage among software development professionals in the FinTech sector. Drawing on technology acceptance and socio-technical perspectives, the study investigates how perceived productivity, performance enhancement, learning and development, trust, and sectoral impact influence actual usage behavior. Data were collected from 154 developers through a structured survey and analyzed using non-parametric statistical methods. The findings indicate that usage frequency and application domain significantly shape general usage and learning perceptions, while gender differences emerge in the trust dimension; education level and professional experience show no statistically significant effects. Overall, the results highlight that contextual engagement, and practical performance benefits play a more decisive role in AI-assisted tool adoption than demographic characteristics, offering implications for structured and domain-specific implementation strategies in regulated software environments.